Pengenaan Retribusi Pembuatan Kartu Tanda Penduduk (KTP) di Persimpangan Jalan - Fajar Iswahyudi (Magister Administrasi Publik, 2012)
Citizen Identity Card (Kartu Tanda Penduduk/KTP) is citizen's right which is guaranted by the constitution. To that end, the Stte or Government has the obligatio to fulfill that right without exeption and discrimination. In light of that, KTP making must be of free of charge. If there are any expenses which citizens pay in the process of obtainingtheir KTPs, the state pr government is duty bound to rimburse them. Any revenues which state or government obtain by charging KTP processing, must be stopped as it constitutes a potential sources of revenue in other sectors while at the same time ensuing that right of citizens to KTP are observed.